2018
DOI: 10.1161/circulationaha.117.030856
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle–Specific Progerin Expression Accelerates Atherosclerosis and Death in a Mouse Model of Hutchinson-Gilford Progeria Syndrome

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(183 citation statements)
references
References 37 publications
12
170
1
Order By: Relevance
“…However, TUDCA did not prolong lifespan in Apoe −/− Lmna G609G/G609G mice with ubiquitous progerin expression. This is in accordance with previous observations that, unlike HGPS patients, these mutant mice apparently die from atherosclerosis‐independent causes, possibly arrhythmias, starvation, and cachexia (Hamczyk et al , ; Kreienkamp et al , ). In contrast to Apoe −/− Lmna G609G/G609G mice, Apoe −/− Lmna LCS/LCS SM22αCre mice most likely die from atherosclerosis‐related causes (Hamczyk et al , ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, TUDCA did not prolong lifespan in Apoe −/− Lmna G609G/G609G mice with ubiquitous progerin expression. This is in accordance with previous observations that, unlike HGPS patients, these mutant mice apparently die from atherosclerosis‐independent causes, possibly arrhythmias, starvation, and cachexia (Hamczyk et al , ; Kreienkamp et al , ). In contrast to Apoe −/− Lmna G609G/G609G mice, Apoe −/− Lmna LCS/LCS SM22αCre mice most likely die from atherosclerosis‐related causes (Hamczyk et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…TUDCA treatment alleviated aortic VSMC loss (Fig A and B), adventitial thickening (Fig C and D), and inhibited atherosclerosis (Fig E and F) in both Apoe −/− Lmna G609G/G609G and Apoe −/− Lmna LCS/LCS SM22αCre mice. Atheromas of TUDCA‐treated progeroid animals showed reduced necrotic core size and increased VSMC content (), indicating an amelioration of the vulnerable plaque phenotype reported previously in these mice (Hamczyk et al , ). We next assessed the effect of a sustained TUDCA treatment on survival in normal chow‐fed progeroid mice.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Considering the role that macrophages have in atherosclerosis, it is surprising that mice with macrophage‐restricted progerin expression did not present with an HGPS phenotype (Hamczyk et al , ). Zhou et al () have shown activation of ER stress/UPR‐related pathways in macrophages recruited to the vascular lesions in ApoE −/− mice, but UPR was mainly triggered by lipid accumulation, at least at later stages.…”
Section: Mechanisms Of Vsmc Loss In Hgps‐dependent Atherosclerosismentioning
confidence: 99%
“…Finally, the authors demonstrate that alleviation of ER stress is sufficient to reduce VSMC loss in the aorta: Indeed, administration of the chemical chaperon tauroursodeoxycholic acid (TUDCA) inhibited pro‐apoptotic gene expression, blunted atherosclerosis progression, and prolonged the lifespan of mice with VSMC‐selective progerin expression (Hamczyk et al , ), which most likely die from atherosclerosis‐related causes (Hamczyk et al , ). This is a particularly important finding since it confirms the therapeutic value of intervening at the two pathways in VSMCs.…”
Section: Mechanisms Of Vsmc Loss In Hgps‐dependent Atherosclerosismentioning
confidence: 99%